1969
DOI: 10.1042/bj1110413
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of ethylene. Methanesulphinic acid as cofactor in the enzymic formation of ethylene from methional

Abstract: The second cofactor in the peroxidase-catalysed formation of ethylene from methional in cauliflower extracts was identified as methanesulphinic acid. The progress of the reaction is described and the activities of related sulphinic acids were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1969
1969
1980
1980

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These enzymes have since been identified as a glucose oxidase and a peroxidase ). The peroxidase utilizes the hydrogen peroxide produced by the oxidase to convert the C-3 and C-4 atoms of methional into ethylene in the presence of two cofactors, a phenolic acid and a sulphinic acid (Mapson & Mead, 1968;Mapson, Self & Wardale, 1969). In the earlier work, we also showed the necessity for the synthesis from methionine of an enzyme present in the mitochondrial-microsomal fraction, and suggested that the function of this enzyme in the synthetic pathW way was to produce a precursor similar to or identical with methional.…”
mentioning
confidence: 99%
“…These enzymes have since been identified as a glucose oxidase and a peroxidase ). The peroxidase utilizes the hydrogen peroxide produced by the oxidase to convert the C-3 and C-4 atoms of methional into ethylene in the presence of two cofactors, a phenolic acid and a sulphinic acid (Mapson & Mead, 1968;Mapson, Self & Wardale, 1969). In the earlier work, we also showed the necessity for the synthesis from methionine of an enzyme present in the mitochondrial-microsomal fraction, and suggested that the function of this enzyme in the synthetic pathW way was to produce a precursor similar to or identical with methional.…”
mentioning
confidence: 99%
“…was added to start the reaction, and the ethylene concentration was determined with a gas chromatograph after 5-min incubation at room temperature. In experiments with crystallized egg albumin, 12 (21) containing MnSO4, resorcinol, NaHSO, KH2P04 (pH 7.8), and horseradish peroxidase was used to measure ethylene production from various concentrations of substrates after 5-min incubation. The initial rates of ethylene evolution were calculated by substracting the rate of the complete system without peroxidase from the rate of the complete system.…”
mentioning
confidence: 99%